The voice in the drum : music, language, and emotion in Islamicate South Asia - Wolf, Richard K., 1962- (University of Illinois Press, 2014)
Based on extensive research in India and Pakistan, this study examines the ways drumming and voices interconnect over vast areas of South Asia and considers what it means for instruments to be voice-like and carry textual messages in particular contexts. Richard K. Wolf employs a hybrid, novelistic form of presentation in which the fictional protagonist Muharram Ali, a man obsessed with finding music he believes will dissolve religious and political barriers, interacts with Wolf's field consultants, to communicate ethnographic and historical realities that transcend the local details of any one person's life.